Learning analytics - Grubelnik, Vladimir (International journal of management, knowledge and learning, 2025)
Purpose: The purpose of this study is to preliminarily verify the concept of personalised and collaborative learning and to formatively observe students' knowledge, skills, problem-solving strategies and social dynamics in the classroom. Study design/methodology/approach: The study was conducted with 8th grade students (N=21) using the ClassRoom Analytica (CRA) application as part of a thematic unit on ionic bonds. Students participated in digitally facilitated group problem-solving activities guided by predefined parameters for accessing information. Findings: The use of the CRA application proved highly beneficial in a heterogeneous class as it was responsive to all students and provided the teacher with detailed information about each individual’s role within the class. Originality/value: This study presents CRA as a novel integration of learning analytics and domain-specific visualisations in the science classroom.
Keywords: analitika učenja; learning analytics; problem-solving; reševanje problemov; social interaction; socialna interakcija